(untitled) (Global Journal of Management and Business Research, 2011)
Mobility, user-friendliness and convenience of communication has made mobile phone an integral part of human life. Past research related to mobile phone reveals that mobile usage pattern varies from one group to another. Hence, by considering these issues relating to the usage pattern of different age-groups, researchers have attempted to carry out an exploratory study of rural youths pursuing graduation from Educational Institutions located in a nearby town- Visnagar in Gujarat State (India). Opinions of students regarding various brands of mobile handsets, mobile operators and functions of mobile phones are being investigated in this paper. The paper emphasizes on different influential factors affecting mobile purchase. If different rural segments are systematically studied and analysed, organisations willing to enter the emerging rural market will be able to promote their products and services in a much better manner leading to higher customer satisfaction and in an increased market size.